APPRAISAL OF MODIFIED ALVARADO SCORE FOR ACUTE APPENDICITIS IN NIGERIA ADULTS - Ashindoitiang John, Dr.; V. C, Dr. Nwagbara; Asuquo, Prof. Maurice (IJRDO -JOURNAL OF HEALTH SCIENCES AND NURSING, 2017)
Decision making in cases of acute appendicitis may be difficult experience in Nigeria where thefacilities for investigations are lacking. Modified Alvarado score (MASS) was very important indiagnosis and treatment of patients with acute appendicitis seen in a semi rural area of LagosNigeria.Method: All adult patients aged 16 and above who were seen with a provisional diagnosis ofacute appendicitis between January 2012 and December 2014 were included in the study. Therewere 35 males and 23 females. The 58 patients were evaluated on admission using modifiedAlvarado score to determine whether they have acute appendicitis. The Alvarado score wascompared with the operative and histology results.Results: Fifty eight patients were operated. The operative findings showed 51 (87.9) has positiveresult for acute appendicitis. While 7 (12.1) had negative findings. However the histology shows44 (75.9) with features of acute appendicitis and 14 (24.1) were negative.Conclusion: The above results shows modified Alvarado score is very sensitive in diagnosis ofacute appendicitis in our environment. It is a very useful tool in absence of facilities in diagnosisof acute appendicitis.